Student engagement, non-completion and pedagogy: Development of a measurement tool. (April 2017) - Dulfer, Nicky; Rice, Suzanne; Clarke, Kira
A significant body of research documents the negative consequences of dropping out of school for both the individual and society. In attempting to respond to the problem of early school leaving, schools and systems internationally have put in place a range of system-level and local responses such as mentoring, targeted additional career guidance and homework clubs. Unfortunately, these 'add-ons' often stop outside the classroom door, and do not consider the impact of teaching practices on students' engagement in school and their decisions to remain or leave. This article reports on the development of instruments aimed at measuring four constructs that have been shown to be related to student engagement and school completion, namely competence, autonomy, relatedness and an appreciation of subject relevance. Analyses of data from a small sample of Year 9 students ( N = 48) in two Australian secondary schools indicated that, with some adjustments, the research instruments developed provided reliable and valid measures of the four constructs for use in large-scale research with students.